Evaluation of outcomes of psychological interventions in terminally ill family caregivers: a brief overview - Rezaei, Masoud; Keyvanloo Shahrestanaki, Sahar; Sheikh Milani, Arezoo; Neishabouri, Masoumeh; Khaleghparast, Shiva; Rajabi, Mohammad Reza (Oncology Reviews, 2024)
Background: Family caregivers play a crucial role in supporting patients with incurable diseases, but often experience significant stress and anxiety. This study aimed to investigate the impact of psychological interventions on family caregivers, with a focus on reducing the burden of care, improving mental health and quality of life, and promoting family communication.: This study conducted a brief overview of quantitative and qualitative research on assessing the impact of psychological interventions on family caregivers. A comprehensive literature search was conducted in PUBMED, SCOPUS, EMBASE, SCIENCE DIRECT and WEB OF SCIENCE to identify relevant papers, resulting in 20 articles being included. The included studies focused on evaluating the outcomes of psychological interventions on family caregivers. Result: Ultimately, 20 relevant articles were retrieved from a pool of 500 articles, focusing on the evaluation of the primary outcomes of psychological interventions on family caregivers. The review of 20 articles revealed that interventions such as expressive writing and reminiscence therapy had a positive and significant impact on reducing the burden of care and fostering a positive care environment. Additionally, these interventions were found to be effective in improving self-esteem, family communication, and overall wellbeing. Conclusion: The study emphasizes the need for further research to confirm the benefits of these interventions and their role in promoting family resilience. These findings highlight the potential of psychological interventions in alleviating the challenges faced by family caregivers of patients with incurable diseases.